2012
DOI: 10.1017/s0033291712000074
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia patients with a history of childhood trauma have a pro-inflammatory phenotype

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 50 publications
2
56
1
4
Order By: Relevance
“…However, if AVH is viewed as often (although not always) being a post-traumatic reaction, then its presence in people with PTSD or borderline personality disorder (in which childhood trauma is common, and where AVH are also phenomenology similar to SZ-AVH; Kingdon et al, 2010) is to be expected. Rather than primarily searching for psychotic subtypes of PTSD or borderline personality disorder, future research may more profitably explore, (a) why trauma leads to AVH in some people but not others); (b) whether there exist trauma-based and non-trauma based subtypes of AVH in schizophrenia, each with a characteristic biological phenotype (such as an inflammatory phenotype in the case of the former; Dennison et al, 2012); and (c) why some AVH are more likely to be complicated by delusional elaboration than others (and are hence more likely to result in a diagnosis of schizophrenia), a process already tentatively linked with environmental risk factors and affective dysregulation (Smeets et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…However, if AVH is viewed as often (although not always) being a post-traumatic reaction, then its presence in people with PTSD or borderline personality disorder (in which childhood trauma is common, and where AVH are also phenomenology similar to SZ-AVH; Kingdon et al, 2010) is to be expected. Rather than primarily searching for psychotic subtypes of PTSD or borderline personality disorder, future research may more profitably explore, (a) why trauma leads to AVH in some people but not others); (b) whether there exist trauma-based and non-trauma based subtypes of AVH in schizophrenia, each with a characteristic biological phenotype (such as an inflammatory phenotype in the case of the former; Dennison et al, 2012); and (c) why some AVH are more likely to be complicated by delusional elaboration than others (and are hence more likely to result in a diagnosis of schizophrenia), a process already tentatively linked with environmental risk factors and affective dysregulation (Smeets et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This is especially interesting in the light of body of research showing repeatedly a shift from Th1 to Th2 immune response in schizophrenia patients, both in vivo and in vitro (Muller et al, 2000a;Schwarz et al, 2001). Interestingly, there are reports showing that elevations in cytokine serum levels in adult schizophrenia patients are correlated with a history of childhood maltreatment (TNF-alpha, IL-6) (Dennison et al, 2012), as well as with recent stressors encounters (IL-1beta, TNF-alpha, IFN-gamma and IL-6) (Di Nicola et al, 2012). Additionally, the extent of traumatic events has been associated with TNF-alpha level (Dennison et al, 2012;Di Nicola et al, 2012), while recent stressful life-events have been found to correlate with higher TNF-alpha mRNA levels in leukocytes of patients with schizophrenia (Di Nicola et al, 2012).…”
Section: Immune and Inflammatory Responsementioning
confidence: 98%
“…Epigenetic research into schizophrenia works primarily with biological mechanisms, processes or features that might be aberrant in schizophrenia, and -despite its characterisation as epigenetic -typically says relatively little about the environmental impacts that might modify them. There are some exceptions, notably diet (Singh, Murphy, & O'Reilly, 2003), smoking (Hillemacher et al, 2008), famine (Lumey, Stein, & Susser, 2011), and trauma (Dennison, McKernan, Cryan, & Dinan, 2012). For the most part, however, the research focuses upon biological, epigenetic pathways and does not specify, or does not quantify, the environmental and social influences that might have modified them.…”
Section: Positioning Epigenetics In Schizophreniamentioning
confidence: 99%